REPRESENTASI SUPERIORITAS PADA IKLAN PROMOSI PERGURUAN TINGGI DI TELEVISI (STUDI SEMIOTIK PIERCE PADA IKLAN BSI GROUP) - Meliala, Robbikal Muntaha (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
This research started by background the phenomenon appearance of negative responses from netizen on promotion advertisement from BSI Group STMIK Nusa Mandiri version of office that has been published in television and youtube since 2016. This advertisement was suspected ignore ethic of Indonesia advertisement 2014 related to the articles 1.20 about underestimate message to other product by humiliating them either direct or indirect way. This research aimed to know how superiority was represented on promotion advertisement from BSI Group in television period 2010-2016, has content humiliating to other products and ignored ethic of communication. Techniques of data collecting are literature reviews and documentations. Research methodology that writer used is semiotic analysis with qualitative approached. Technique of data analysis that writer used is semiotic model of Charles S. Pierce with his meaning triangle consist of: sign, object and interpretent. 6 audio visual advertisements were chosen by the writer with purposive sampling. Research result has shown the superiority was represented in many way, they are superlative language usage which exposed the word of quality number one as a campus without research evidence earlier. The usage of story idea which compare between quality of BSI Graduatee Group who more proper to be manager, productive director at office than the quality of non BSI Graduatee Group.BSI Group pretend to promote by frontal humor in their advertisements to the audience.